Identification of Collagenolytic Bacteria in Human Samples: Screening Methods and Clinical Implications for Resolving and Preventing Anastomotic Leaks and Wound Complications. Issue 8 (August 2019) - Guyton, Kristina L.; Levine, Zoe C.; Lowry, Ann C.; Lambert, Laura; Gribovskaja-Rupp, Irena; Hyman, Neil; Zaborina, Olga; Alverdy, John
Abstract : BACKGROUND: Bacteria that produce collagen-digesting enzymes (collagenolytic bacteria) have been shown to play a critical and previously unappreciated role in anastomotic leak pathogenesis by breaking down host tissue extracellular matrix proteins. Detection of these bacteria is labor intensive, and no screening method currently exists. OBJECTIVES: We evaluated a rapid screening method developed to detect the presence of these collagenolytic bacteria in clinical samples, such as drain fluid, anastomotic tissue, or feces. DESIGN: We compared a new method of detecting collagenolytic bacterial species with a previously used technique using samples from a murine experimental model and then demonstrated the utility of this screening method in samples from patients with anastomotic complications. SETTINGS: All of the laboratory work and previous murine experiments were performed in Dr Alverdy's laboratory at the University of Chicago under institutional review board–approved protocols. PATIENTS: Samples from patients with challenging wound complications were provided by participating clinicians with verbal patient consent. Given the small number of patients, this was determined to be institutional review board exempt. MAIN OUTCOME MEASURES: Whether this analysis can influence patient management and outcomes will require additional study. RESULTS: This screening method detects numerous strains of bacteria with collagenolytic properties, including the collagenolytic species that have been implicated previously in anastomotic leak. Once collagenolytic strains are identified, they can be speciated and tested for antibiotic resistance using standard laboratory techniques. LIMITATIONS: This study is limited by the small number of patient samples tested. CONCLUSIONS: We demonstrated the potential applicability of this assay to evaluate rare and complex anastomotic complications that often require analysis beyond standard culture and sensitivity assays. Future applications of this method may allow the development of strategies to prevent anastomotic leak related to collagenolytic bacteria. SeeVideo Abstract athttp://links.lww.com/DCR/A962 .